X-ray Photoelectron Spectroscopy for Probing Non-bridging Oxygen in Silver Ion Conductors and their Relationship to Ionic Conductivity - E.B, Saniman; M.Z.A, Yahya; A.K, Arof (Malaysian Journal of Science, 2002)
The materials studied in this work are 60AgI-20Ag_2O-20[0.1M_mO_n + 0.9MÃ¢â‚¬â„¢_m’O_n’] of the boron oxide rich glass with M_mO_n as WO_3 and MÃ¢â‚¬â„¢_m’O_n’ as B_2O_3 and the WO_3 rich glass with M_mO_n as B_2O_3 and MÃ¢â‚¬â„¢_m’O_n’ as WO_3. XPS has shown that for glasses with the same amount of network modifiers glasses with a higher electrical conductivity have a larger number of (non-bridging oxygen) NBOs. This experiment helped in the deduction of the formation of tetrahedral oxyanions which when share corners with one another could result in the formation of larger channel-like pathways or Ã¢â‚¬Å“open structuresÃ¢â‚¬Â in the glasses through which more silver ions can flow through with ease.